Stereotactic Body Radiation Therapy in Oligometastatic Ovarian Cancer: A Promising Therapeutic Approach. Issue 8 (October 2018) - Iftode, Cristina; D'Agostino, Giuseppe R.; Tozzi, Angelo; Comito, Tiziana; Franzese, Ciro; De Rose, Fiorenza; Franceschini, Davide; Di Brina, Lucia; Tomatis, Stefano; Scorsetti, Marta
Abstract : Objective: Stereotactic body radiation therapy (SBRT) has been successfully used to treat oligometastases of several primary tumors, but few experiences have been described in patients with gynecological oligometastatic cancer, particularly in ovarian neoplasm. The aim of this study was to evaluate the role of this new radiotherapy modality in a series of oligometastatic ovarian cancer patients. Materials and Methods: Clinical records of patients affected by oligometastatic ovarian carcinoma treated with SBRT were reviewed. Results: Twenty-six patients with 44 metastatic lesions (lymph nodes, 63.6%; liver, 31.8%; and lung, 4.5%) treated with SBRT between January 2011 and May 2017 were analyzed. After a median follow-up period of 28.5 months (range, 6–86 months), 17 patients (65.4%) were still alive at time of analysis: 6 are without evidence of disease, 11 experienced a disease progression. Eight patients died of disease, 1 died because of an heart attack while being disease free. The median local control (LC) was not reached. One-, 2-, and 5-year LCs were 92.9%. Median progression-free survival was 19 months, with 1-year progression-free survival of 69.3% and 38% at 2 years, 19% at 5 years. Median overall survival was 64.5 months, with all patients alive after 1 year, 92.7% at 2 years, and 61.7% at 5 years. Five (11.3%) cases experienced G2 toxicity; most common adverse effect was nausea and vomiting (3 cases [6.8%]) followed by abdominal pain (2 cases [4.5%]). None of the patients had grade 3 or grade 4 acute or late toxicity. Conclusions: In conclusion, SBRT is a feasible and safe approach for selected cases of oligometastatic ovarian cancer, with satisfactory results in terms of LC and disease free survival.